HUBUNGAN PENERAPAN PIJAT PERINEUM UNTUK MENGURANGI RUPTUR PERINEUM SAAT PERSALINAN DI KLINIK PRATAMA RATNA KOMALA TAHUN 2020 - Siregar, Renince (Jurnal Ayurveda Medistra, 2021)
The incidence of perineal lacerations needs to be prevented, one of which is perineal massage. The perineum is the area of ​​skin between the vaginal canal and the anus (anus) which can be torn during childbirth (Herdiana, 2014). Perineal massage is one of the oldest and surest ways to promote healthy blood flow, elasticity, and relaxation of the pelvic floor muscles (Hadiningsih 2014:155). This study aims to determine "the relationship between the application of perineal massage to reduce perineal rupture during labor at the Ratna Komala Primary Clinic in 2020". The population used in this study were all mothers who took part in the perineal massage class 50 people in the period in May 2020. The sample in this study were mothers who took part in the application of self-perineal massage when the study began in May and maternity mothers who had complete data with sampling method using total sampling technique. The results of this study indicate that there is a relationship between the application of perineal massage to reduce perineal rupture during delivery, this can be seen from the results of the study, the value of p = 0.002 (p <0.05). It is expected that pregnant women who are nearing delivery will take an antenatal class on the application of perineal massage so that the delivery process can run according to the condition or is still in good condition, and reduce the occurrence of perineal rupture or episiotomy.